Role of fungi in bioremediation of emerging pollutants - Vaksmaa, Annika; Guerrero-Cruz, Simon; Ghosh, Pooja; Zeghal, Emna; Hernando-Morales, Victor; Niemann, Helge (Frontiers in Marine Science, 2023)
Advancements in chemical, medical, cosmetic, and plastic producing industries have improved agricultural yields, health and human life in general. As a negative consequence, a plethora of chemicals are intentionally and unintentionally released to terrestrial and aquatic environments with sometimes devastating effects for entire ecosystems. One mitigation strategy to counteract this pollution is bioremediation. Bioremediation is an umbrella term for biologically mediated processes during which an undesired compound is transformed, degraded, sequestered and/or entirely removed from the ecosystem. Organisms across all domains of life may mediate bioremediation; yet, fungi are particularly promising candidates. They possess metabolic capabilities to break down complex molecules which make fungi the ultimate degraders of recalcitrant organic matter in nature. Bioremediation by fungi, also termed mycoremediation, has been more frequently investigated in terrestrial than aquatic ecosystems, although fungi also thrive in lacustrine and marine environments. Here, we focus on mycoremediation of emerging pollutants in aquatic environments. In this context, we draw parallels between terrestrial and aquatic fungal taxa, and their role in mycoremediation. We discuss the ability of fungi to break-down (i) pesticides, (ii) pharmaceuticals and personal care products, (iii) plastics, both conventional types and (iv) bioplastics, and fungal role, (v) mitigation of heavy metal pollution. Furthermore, we (vi) discuss possible mycoremediation strategies in applied settings and highlight novel enzyme based mycoremediation strategies.